PENANAMAN NILAI MORAL PADA ANAK USIA DINI OLEH ORANG TUA DALAM KELUARGA DI JORONG KOTO ALAM - Rakimahwati Rakimahwati; Indah Kemala dewi (Early Childhood: Jurnal Pendidikan, 2021)
the background of this research is the number of early childhood who behave and behave not in accordance with values ??and morals. This study aims to find out how the cultivation of moral values ??in early childhood by parents in the family in Jorong Koto Alam. The type of this research is descriptive research using a qualitative approach. To see how the Cultivation of Moral Values ??in early childhood by parents in families in Jorong Koto alam. The research subjects were parents in the family in Jorong Koto alam. The research subjects were parents in the family in Jorong Koto alam. Data collection techniques used in the form of observation, interviews and documentation. The data analysis technique followed the steps of Miles and Huberman, namely data collection, data reduction, data presentation, and verification. Meanwhile, the data validation technique used was triangulation technique. The results of the study generally show that the cultivation of moral values ??in early childhood is carried out by teaching good and bad, manners, and how to worship. Parents are examples and models for early childhood so that children behave in accordance with their morals. Supporting factors for planting moral values ??are high children's obedience to parents, parents' expectations that children behave well, attention from parents, religious learning, and napping habits. While the inhibiting factors for the cultivation of moral values ??are a poor environment, limited time for parents to meet children, and no examples of good behavior from parents, and the absence of social restrictions.